The Association Between High-Density Lipoprotein Levels and the Incidence of Acute Coronary Syndrome at RSUD Buleleng - NI PUTU MEILIA MARTHA AYUNI (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2026)
Background: Cardiovascular diseases remain the leading cause of mortality worldwide, with Acute Coronary Syndrome (ACS) as the most threatening manifestation. High-density lipoprotein (HDL) has protective effects through reverse cholesterol transport, as well as anti-inflammatory, antioxidant, and antithrombotic functions. Low HDL levels are suspected to increase the risk of ACS. This study aims to determine the association between HDL levels and the occurrence of ACS at Buleleng General Hospital. Method: This study employed a cross-sectional design involving 108 patients admitted to the ICVCU of Buleleng General Hospital during January–June 2024, comprising ACS and non-ACS groups. Data were obtained from medical records, including patient characteristics and lipid profile results. Statistical analysis was performed using the Chi-square test. Results: Out of 108 patients, 75 (69.4%) were diagnosed with ACS, while 33 (30.6%) were classified as non-ACS. Most ACS patients had low HDL levels (64.0%), whereas the majority of non-ACS patients had normal HDL levels (69.7%). The Chi-square analysis demonstrated a significant association between HDL levels and ACS events (p = 0.001). Discussion: The findings indicate that low HDL levels can increase the risk of developing ACS. This result aligns with existing theories and previous studies highlighting the protective role of HDL in cardiovascular health. Conclusion: HDL levels are significantly associated with ACS occurrence. Low HDL increases the risk of atherosclerosis, while normal or high HDL levels provide a protective effect. Lipid profile evaluation, particularly HDL levels, is essential for individuals at high risk as part of early preventive strategies.